Figurative World of Poem by Taras Shevchenko “A Meditation (Water Is Flowing to the Blue Sea…)” and the Peculiarities of its Recreation in Crimean Tatar Translation - Viktor I. Humeniuk (Studia Litterarum, 2022)
Crimean Tatar translations of Taras Shevchenko’s poetic compositions are most perfectly represented in Simferopol publications as “Saylama sheerler” [“The elected Works”] (1940) and “Far and Near – Uzaq ve yaqyn – Shevchenko” (1999). A substantial contribution to this sphere was done particularly by such modern poets as Isa Abduraman, Yunus Kandym, Shakir Selim. Ablyaziz Veliyey is also among them, being the author of the poetical interpretations of such Shevchenko’s lyrics as “Don’t marry the rich one,” “Mother Gave Birth to Me” and also “A meditation (Water Is Flowing to the Blue Sea…).” The last composition and the comparison of it with Crimean Tatar translation is the main object of studying in the suggested publication. Personality of the stranger, who endures the ordeals at foreign land and thinks about his misfortune, being at sea coast, is in the centre of the composition. Laconically impressive metaphorical-picturesque imagery is characteristic to the poetics of this work. Permanent association of water flowing with irreversible flying of time is connected here with the poetic thoughts about the difficulties of human’s destiny. Genre-stylistic, versification, image-composition and other peculiarities of the origin are conveyed appropriately in Crimean Tatar interpretation by A. Veliyev. Conveying these peculiarities, the translator absolutely in accordance to the poetics of the origin, tactfully and spectacularly appeals to the poetic means of folk song.